Особенности пунктуации при слове действительно Osobennosti punktuatsii pri slove dejstvitelno - Budanova Tamara (Wydawnictwo Uniwersytetu Jagiellońskiego, 2022)
The paper examines punctuation features of the word dejstvitelʹno.   It is suggested that tendencies in using punctuation marks to single it out in texts correlate with the context determined functional polysemy of discourse words.